Complex Investigation of the Fermi Surface in HfB₂ - Sichkar, S.M.; Antonov, V.N. (Металлофизика и новейшие технологии, 2015)
The electronic structure, Fermi surface, angle dependence of the cyclotron masses, and extremal cross sections of the Fermi surface of the hafnium diboride are investigated from the first principles using the fully relativistic and full-potential linear muffin-tin orbitals’ methods. A good agreement with experimental data of cyclotron masses and extremal cross sections of the Fermi surface is achieved. Електронну структуру, поверхню Фермі, кутову залежність циклотронних мас і екстремальні перетини поверхні Фермі дибориду гафнію було досліджено з перших принципів із використанням повністю релятивістського та повнопотенціяльного методів лінійних МТ-орбіталей. Було досягнуто задовільного збігу з експериментальними даними стосовно циклотронних мас і екстремальних перетинів поверхні Фермі. Электронная структура, поверхность Ферми, угловая зависимость циклотронных масс и экстремальные сечения поверхности Ферми диборида гафния были исследованы из первых принципов с использованием полностью релятивистского и полнопотенциального методов линейных МТ-орбиталей. Было достигнуто хорошее согласие с экспериментальными данными циклотронных масс и экстремальных сечений поверхности Ферми.